A temporary plugging material composition, a preparation method and application in fracturing of low-temperature oil and gas reservoirs

CN122959004APending Publication Date: 2026-10-23CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510511463.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是在低温油气藏条件下的降解速率十分缓慢,无法满足现场压裂施工要求,严重影响油气产量

Benefits of technology

[0016]本发明提高了PGA暂堵材料在低温油气田下的降解速率,满足油气田现场施工要求,实现压裂暂堵增压、转向扩缝、转向压裂、降解速率可控的效果,达到提升油气田产量的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005371727340000101
    Figure BDA0005371727340000101
Patent Text Reader

Abstract

The application belongs to the field of oil and gas reservoir fracturing, and discloses a temporary plugging material composition, a preparation method and application in low-temperature oil and gas reservoir fracturing. The temporary plugging material composition comprises polyglycolic acid, a wicking agent and a promoter. The wicking agent is a water-absorbing bio-based material, and the promoter is a slow-release alkali. The application improves the degradation rate of the PGA temporary plugging material in low-temperature oil and gas fields, meets the requirements of oil and gas field construction, realizes the effects of fracturing temporary plugging, pressure boosting, diversion and fracture expansion, diversion fracturing and controllable degradation rate, and achieves the purpose of improving the output of oil and gas fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oil and gas reservoir fracturing, and more specifically, relates to a temporary plugging material composition and its preparation method and its application in low-temperature oil and gas reservoir fracturing. Background Technology

[0002] To ensure energy security and improve crude oil self-sufficiency, increasing the exploration and development of oil and natural gas is one of the most effective measures. During exploration and development, effective fracturing of oil reservoirs is a crucial technology for increasing crude oil production capacity, especially multi-stage fracturing.

[0003] To achieve effective transmission and redirection of fracturing fluid pressure, highly degradable and controllable temporary plugging materials play a crucial role. In fracturing technology, the first-stage fracture must be temporarily plugged to enable second, third, and subsequent multi-stage fracturing. Simultaneously, highly degradable and controllable temporary plugging materials also play a key role in the repeated fracturing, integrated management, and water control and oil stabilization in old oilfields. During staged fracturing and reservoir stimulation, these materials can alter the original fracture extension direction, constructing new fracture systems. After fracturing, the temporary plugging material can autonomously and completely degrade, releasing the original fractures without harming or polluting the formation. This provides strong technical support for the sustainable development of oil and gas reservoirs and significantly increasing oil and gas production. Specifically, the temporary plugging material enters the existing fractures or high-permeability zones of the borehole, generating a high-strength filter cake bridge. This forces the static pressure within the fracture to rise above the formation fracturing pressure, preventing subsequent fracturing fluid from entering the original fractures and high-permeability zones. Instead, it enters high-stress zones or new fracture layers, leading to the formation of new fractures.

[0004] Currently, these temporary plugging materials are characterized by good plugging effect and pressure resistance under specific reservoir conditions, but they lack biodegradability or have poor biodegradability, requiring complex processes such as subsequent unplugging. They also cause significant damage to the formation, and the temporary plugging time is uncontrollable, seriously affecting oil and gas field productivity.

[0005] Polyglycolic acid (PGA) is a novel biodegradable material that degrades rapidly in high-temperature (90℃) and aqueous environments. It has seen initial applications as a temporary plugging material in high-temperature oil and gas fields, achieving good oil production and economic benefits. However, its degradation rate is extremely slow under low-temperature oil and gas reservoir conditions, failing to meet the requirements of in-situ fracturing operations and severely impacting oil and gas production. Therefore, effectively controlling the degradation rate of PGA materials to achieve rapid degradation under low-temperature (≤50℃) oil and gas conditions can provide technical support for the exploration and development of low-temperature oil and gas fields. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a temporary plugging material composition, its preparation method, and its application in fracturing of low-temperature oil and gas reservoirs. This invention improves the degradation rate of PGA temporary plugging materials in low-temperature oil and gas fields, meeting the requirements of on-site construction in oil and gas fields. It achieves the effects of pressure enhancement through temporary plugging, fracture widening, and controlled degradation rate, thereby increasing oil and gas field production.

[0007] To achieve the above objectives, a first aspect of the present invention provides a temporary plugging material composition comprising polyglycolic acid, an absorbent, and an accelerator;

[0008] The absorbent is a water-absorbing bio-based material;

[0009] The accelerator is a slow-release alkali.

[0010] A second aspect of the present invention provides a method for preparing the aforementioned temporary plugging material composition, comprising the following steps:

[0011] S1: Polyglycolic acid and a permeating agent are stirred, mixed, melt-blended, and extruded to obtain the extruded material;

[0012] S2: The extruded material is sequentially cooled, granulated, dried and ground to obtain composite material particles;

[0013] S3: The composite material particles are stirred and mixed with the accelerator to obtain the temporary plugging material composition.

[0014] A third aspect of the present invention provides the application of the aforementioned temporary plugging material composition in fracturing of low-temperature oil and gas reservoirs.

[0015] The beneficial effects of the technical solution of the present invention are as follows:

[0016] This invention improves the degradation rate of PGA temporary plugging material in low-temperature oil and gas fields, meets the requirements of on-site construction in oil and gas fields, and achieves the effects of pressure boosting through temporary plugging, crack widening, crack widening, and controllable degradation rate, thereby increasing oil and gas field production.

[0017] The present invention can determine the particle size of the temporary plugging material composition according to the oil and gas field conditions and fracturing operation requirements (e.g., formation permeability and fracture size); the temporary plugging material composition of the present invention has good compatibility with the fracturing fluid used in the oil and gas field operation and can be mixed online, with significant effects of temporary plugging pressurization and directional fracturing.

[0018] The present invention first mixes two components, polyglycolic acid and a permeating agent, then performs melt blending modification, followed by granulation, drying and post-processing to obtain composite material particles of different particle sizes, and finally blends the composite material particles with an accelerator at high speed to obtain a temporary plugging material composition for fracturing in low-temperature oil and gas reservoirs.

[0019] This invention, through the synergistic effect of an absorbent and a promoter, enables a temporary plugging material composition for fracturing to achieve temporary plugging pressurization, directional fracture widening, directional fracturing, and rapid degradation under cryogenic reservoir conditions, meeting the requirements of field construction in cryogenic oil and gas fields. Specifically: the absorbent is a highly absorbent bio-based material with superior water absorption and good diffusivity. After blending and modification with PGA, it can disrupt the original crystalline structure of PGA, significantly reducing its crystallinity and promoting PGA hydrolysis and degradation. Furthermore, upon contact with water, the absorbent rapidly adsorbs water molecules, forming microchannels within the material, thereby enhancing the permeability and diffusivity of water molecules and facilitating hydrolysis and degradation. The promoter is a slow-release alkali that is slowly released 2-4 hours after injection into the formation, providing an alkaline environment for the hydrolysis and degradation of PGA, neutralizing the glycolic acid generated during degradation, and promoting a rapid positive trend in the hydrolysis and degradation equilibrium, thus significantly increasing the PGA degradation rate. Therefore, this invention, through the synergistic effect of the absorbent and promoter, enables the rapid degradation of PGA temporary plugging materials under cryogenic oil and gas reservoir conditions.

[0020] The temporary plugging material composition for fracturing in low-temperature oil and gas reservoirs of the present invention exhibits high impact resistance and high pressure resistance under low-temperature (≤50℃) oil and gas field geological conditions, with a pressure resistance exceeding 45MPa and a pressure-bearing time greater than 4 hours, achieving the purpose and effect of temporarily plugging and redirecting fracturing of new fractures. When the temporary plugging material composition is injected into the formation fracture with fracturing fluid, its degradation accelerates after 4 hours under low-temperature oil and gas reservoir conditions, and it can achieve almost complete degradation within 48 hours, leaving less than 5% residue after degradation. This eliminates the need for unplugging and causes no damage to the formation, significantly improving oil and gas well productivity. Therefore, the temporary plugging material composition for fracturing in low-temperature oil and gas reservoirs of the present invention can provide important technical support for increasing efficiency and profitability in the exploration and development of low-temperature oil and gas fields.

[0021] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation

[0022] Preferred embodiments of the invention will now be described in more detail. While preferred embodiments of the invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that the invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.

[0023] To achieve the above objectives, a first aspect of the present invention provides a temporary plugging material composition comprising polyglycolic acid, an absorbent, and an accelerator;

[0024] The absorbent is a water-absorbing bio-based material;

[0025] The accelerator is a slow-release alkali.

[0026] In this invention, "controllable degradation rate" means that the degradation of the temporary plugging material composition is accelerated in low-temperature oil and gas fields.

[0027] In a specific embodiment, based on the total mass of the temporary plugging material composition, the mass percentage of polyglycolic acid is 84-90%, the mass percentage of the permeation agent is 5-15%, and the mass percentage of the accelerator is 1-5%.

[0028] According to a preferred embodiment of the present invention, the polyglycolic acid is a homopolymer obtained by ring-opening polymerization of glycolide, and / or a copolymer obtained by copolymerization of glycolide and functional monomers.

[0029] According to a preferred embodiment of the present invention, the functional monomer is lactide.

[0030] In a specific embodiment, the number-average molecular weight of the polyglycolic acid is between 30,000 and 120,000.

[0031] In a specific embodiment, the absorbent is at least one of starch, carboxymethyl cellulose, and gelatin.

[0032] In a specific embodiment, the slow-release alkali is sodium tripolyphosphate.

[0033] A second aspect of the present invention provides a method for preparing the aforementioned temporary plugging material composition, comprising the following steps:

[0034] S1: Polyglycolic acid and a permeating agent are stirred, mixed, melt-blended, and extruded to obtain the extruded material;

[0035] S2: The extruded material is sequentially cooled, granulated, dried and ground to obtain composite material particles;

[0036] S3: The composite material particles are stirred and mixed with the accelerator to obtain the temporary plugging material composition.

[0037] According to a preferred embodiment of the present invention, in step S1: the stirring and mixing rate is 50-200 r / min, and the time is 5-10 min.

[0038] According to a preferred embodiment of the present invention, in step S1: the melt blending is carried out in a twin-screw extruder, the temperature of the twin-screw extruder is 200-230°C, and the residence time of the material in the twin-screw extruder is 5-10 min.

[0039] According to a preferred embodiment of the present invention, the grinding equipment is an impact mill.

[0040] According to a preferred embodiment of the present invention, in step S2, the median particle size of the composite material particles is 80-2000 μm.

[0041] According to a preferred embodiment of the present invention, in step S3, the stirring and mixing rate is 200-300 r / min and the time is 5-10 min.

[0042] In this invention, in steps S1-S3, the extruded material is a thin strip-shaped material, which is rapidly cooled with water, then granulated and dried using a granulator to obtain composite material granules. These granules are then processed by an impact mill to obtain composite material particles with a median particle size (D50) between 80-2000 μm, and whose size is adjustable and controllable. Therefore, it can be seen that the median particle size (D50) of the temporary plugging material composition obtained by mixing and stirring the composite material particles with an accelerator is also between 80-2000 μm.

[0043] A third aspect of the present invention provides the application of the aforementioned temporary plugging material composition in fracturing of low-temperature oil and gas reservoirs.

[0044] According to a preferred embodiment of the present invention, the temperature of the low-temperature oil and gas reservoir is ≤50°C.

[0045] In the following embodiments and comparative examples:

[0046] Polyglycolic acid is a homopolymer obtained by ring-opening polymerization of glycolide, an injection molding grade product, purchased from Inner Mongolia Pujing Chemical Co., Ltd.

[0047] The test was conducted on a core flow test apparatus according to the test methods in Q / SH CG0152—2021, "Technical Requirements for Water-Soluble Polymer Temporary Plugging Agents and Temporary Plugging Balls in Fracturing and Acidizing".

[0048] Example 1

[0049] This embodiment provides a temporary plugging material composition, which includes 900g of polyglycolic acid (molecular weight 100,000), 50g of an absorbent and 50g of an accelerator;

[0050] The penetrant is starch;

[0051] The accelerator is sodium tripolyphosphate.

[0052] The preparation method of the temporary plugging material composition in this embodiment includes the following steps:

[0053] Step 1: Add polyglycolic acid and permeation agent into a high-speed mixer, mix at 100 rpm for 5 minutes to obtain a mixture;

[0054] Step 2: The above mixture is injected into a twin-screw extruder for melt blending. The temperature of the twin-screw extruder is 220°C, the material residence time is 7 minutes, and the material is extruded into thin strips.

[0055] Step 3: After the extruded fine strip material is rapidly cooled with water, it is granulated and dried by a granulator to obtain composite material granules;

[0056] Step 4: The above composite material particles are processed by an impact mill to obtain a median particle size (D50) of 500 μm;

[0057] Step 5: Mix the above-mentioned composite material particles and accelerator in a high-speed mixer at 200 r / min for 10 min to obtain the temporary plugging material composition.

[0058] Tests showed that the temporary plugging material composition of this embodiment had a temporary plugging pressure of 45.8 MPa at 50°C, a pressure-bearing time of more than 4 hours, and a residue of 2.2% after degradation after 48 hours (based on the total weight of the temporary plugging material composition).

[0059] Example 2

[0060] This embodiment provides a temporary plugging material composition, which includes 840g of polyglycolic acid (molecular weight 50,000), 150g of an absorbent and 10g of an accelerator.

[0061] The penetrant is carboxymethyl cellulose;

[0062] The accelerator is sodium tripolyphosphate.

[0063] The preparation method of the temporary plugging material composition in this embodiment includes the following steps:

[0064] Step 1: Add polyglycolic acid and permeation agent into a high-speed mixer, mix at 50 r / min for 10 min to obtain a mixture;

[0065] Step 2: The above mixture is injected into a twin-screw extruder for melt blending. The temperature of the twin-screw extruder is 210°C and the material residence time is 10 minutes to extrude fine strip-shaped material.

[0066] Step 3: After the extruded fine strip material is rapidly cooled with water, it is granulated and dried by a granulator to obtain composite material granules;

[0067] Step 4: The above composite material granules are processed by an impact mill to obtain a median particle size (D50) of 100 μm;

[0068] Step 5: Mix the above-mentioned composite material particles and accelerator in a high-speed mixer at 250 r / min for 10 min to obtain the temporary plugging material composition.

[0069] Tests showed that the temporary plugging material composition of this embodiment had a temporary plugging pressure of 57.7 MPa at 30°C, a pressure-bearing time of more than 4 hours, and a residue of 4.1% after degradation after 48 hours (based on the total weight of the temporary plugging material composition).

[0070] Example 3

[0071] This embodiment provides a temporary plugging material composition, which includes 860g of polyglycolic acid (molecular weight 80,000), 100g of permeation agent and 40g of accelerator;

[0072] The penetrant is gelatin;

[0073] The accelerator is sodium tripolyphosphate.

[0074] The preparation method of the temporary plugging material composition in this embodiment includes the following steps:

[0075] Step 1: Add polyglycolic acid and permeation agent into a high-speed mixer, mix at 150 r / min for 8 min to obtain a mixture;

[0076] Step 2: The above mixture is injected into a twin-screw extruder for melt blending. The temperature of the twin-screw extruder is 230°C and the material residence time is 15 minutes to extrude fine strip-shaped material.

[0077] Step 3: After the extruded fine strip material is rapidly cooled with water, it is granulated and dried by a granulator to obtain composite material granules;

[0078] Step 4: The above composite material particles are processed by an impact mill to obtain a median particle size (D50) of 830 μm;

[0079] Step 5: Mix the above-mentioned composite material particles and accelerator in a high-speed mixer at 300 r / min for 9 min to obtain the temporary plugging material composition.

[0080] Tests showed that the temporary plugging material composition of this embodiment had a temporary plugging pressure of 55.4 MPa at 35°C, a pressure-bearing time of more than 4 hours, and a residue of 3.6% after degradation after 48 hours (based on the total weight of the temporary plugging material composition).

[0081] Example 4

[0082] This embodiment provides a temporary plugging material composition, which includes 875g of polyglycolic acid (molecular weight 80,000), 95g of an absorbent and 30g of an accelerator.

[0083] The penetrant is carboxymethyl cellulose;

[0084] The accelerator is sodium tripolyphosphate.

[0085] The preparation method of the temporary plugging material composition in this embodiment includes the following steps:

[0086] Step 1: Add polyglycolic acid and permeation agent into a high-speed mixer, mix at 100 r / min for 9 min to obtain a mixture;

[0087] Step 2: The above mixture is injected into a twin-screw extruder for melt blending. The temperature of the twin-screw extruder is 200°C and the material residence time is 10 minutes to extrude fine strip-shaped material.

[0088] Step 3: After the extruded fine strip material is rapidly cooled with water, it is granulated and dried by a granulator to obtain composite material granules;

[0089] Step 4: The above composite material particles are processed by an impact mill to obtain a median particle size (D50) of 1700 μm;

[0090] Step 5: Mix the above-mentioned composite material particles and accelerator in a high-speed mixer at 250 r / min for 6 min to obtain the temporary plugging material composition.

[0091] Tests showed that the temporary plugging material composition of this embodiment had a temporary plugging pressure of 50.6 MPa at 45°C, a pressure-bearing time of more than 4 hours, and a residue of 2.7% after degradation after 48 hours (based on the total weight of the temporary plugging material composition).

[0092] Comparative Example 1

[0093] The only difference between this comparative example and Example 2 is that the amount of each component is different. Specifically, the temporary plugging material composition of this comparative example includes 840g of polyglycolic acid (molecular weight 50,000), 0g of permeabilizer, and 10g of accelerator.

[0094] Tests showed that the temporary plugging material composition of this comparative example had a temporary plugging pressure of 58.8 MPa at 30°C, a pressure bearing time of more than 4 hours, and a residue of 40.2% after degradation after 48 hours (based on the total weight of the temporary plugging material composition).

[0095] Comparative Example 2

[0096] The only difference between this comparative example and Example 2 is that the amount of each component is different. Specifically, the temporary plugging material composition of this comparative example includes 840g of polyglycolic acid (molecular weight 50,000), 150g of permeabilizer, and 0g of accelerator.

[0097] Tests showed that the temporary plugging material composition of this comparative example had a temporary plugging pressure of 58.3 MPa at 30°C, a pressure-bearing time of more than 4 hours, and a residue of 52.7% after degradation after 48 hours (based on the total weight of the temporary plugging material composition).

[0098] Comparative Example 3

[0099] The only difference between this comparative example and Example 2 is that this comparative example uses only 1000g of polyglycolic acid (molecular weight 100,000).

[0100] Tests showed that the temporary plugging material composition of this comparative example had a temporary plugging pressure of 60 MPa at 30°C, a pressure bearing time of more than 4 hours, and a residue of 85.5% after degradation after 48 hours (based on the total weight of the temporary plugging material composition).

[0101] The test results of the various embodiments and comparative examples are summarized in Table 1.

[0102] Table 1

[0103]

[0104] As shown in Table 1, the temporary plugging material composition for low-temperature oil and gas reservoir fracturing of the present invention has high impact resistance and high pressure resistance under low-temperature (≤50℃) oil and gas field geological conditions. The pressure resistance is higher than 45MPa, the pressure bearing time is greater than 4 hours, and the residue after 48 hours of degradation is <5%, thus achieving the purpose and effect of temporarily plugging new fractures in diversion fracturing.

[0105] Furthermore, as can be seen from the phrase "pressure bearing time greater than 4 hours", the pressure bearing capacity of the temporary plugging material composition for fracturing of the present invention begins to decrease after about 4 hours when it is injected into the formation fracture with fracturing fluid, which meets the requirements of on-site construction. In other words, the temporary plugging material composition for fracturing of the present invention begins to degrade after about 4 hours under low temperature oil and gas reservoir conditions.

[0106] The fracturing temporary plugging material composition of the present invention can achieve almost complete degradation within 48 hours, indicating that the fracturing temporary plugging material composition of the present invention has a fast degradation rate, which is faster than that of polyglycolic acid alone; the residue after degradation is less than 5%, no unplugging is required, and it does not damage the formation, which can significantly improve the productivity of oil and gas wells.

[0107] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A temporary plugging material composition, characterized in that, The temporary plugging material composition includes polyglycolic acid, an absorbent, and an accelerator; The absorbent is a water-absorbing bio-based material; The accelerator is a slow-release alkali.

2. The temporary plugging material composition according to claim 1, wherein, Based on the total mass of the temporary plugging material composition, the mass percentage of polyglycolic acid is 84-90%, the mass percentage of the absorbent is 5-15%, and the mass percentage of the accelerator is 1-5%.

3. The temporary plugging material composition according to claim 1, wherein, The polyglycolic acid is a homopolymer obtained by ring-opening polymerization of glycolide, and / or a copolymer obtained by copolymerization of glycolide and functional monomers; The functional monomer is lactide; The number-average molecular weight of the polyglycolic acid is between 30,000 and 120,000.

4. The temporary plugging material composition according to claim 1, wherein, The penetrant is at least one of starch, carboxymethyl cellulose, and gelatin.

5. The temporary plugging material composition according to claim 1, wherein, The slow-release alkali is sodium tripolyphosphate.

6. A method for preparing the temporary plugging material composition according to any one of claims 1-5, characterized in that, The preparation method includes the following steps: S1: Polyglycolic acid and a permeating agent are stirred, mixed, melt-blended, and extruded to obtain the extruded material; S2: The extruded material is sequentially cooled, granulated, dried and ground to obtain composite material particles; S3: The composite material particles are stirred and mixed with the accelerator to obtain the temporary plugging material composition.

7. The method for preparing the temporary plugging material composition according to claim 6, wherein, In step S1: The stirring and mixing rate is 50-200 r / min, and the time is 5-10 min; The melt blending is carried out in a twin-screw extruder at a temperature of 200-230°C, with the material residence time in the twin-screw extruder being 5-10 minutes.

8. The method for preparing the temporary plugging material composition according to claim 6, wherein, The grinding equipment used is an impact mill; In step S2, the median particle size of the composite material particles is 80-2000 μm.

9. The method for preparing the temporary plugging material composition according to claim 6, wherein, In step S3, the stirring rate is 200-300 r / min and the time is 5-10 min.

10. The application of the temporary plugging material composition according to any one of claims 1-5 in the fracturing of low-temperature oil and gas reservoirs; Preferably, the temperature of the low-temperature oil and gas reservoir is ≤50℃.